The Characteristics of Educator in Surah Al-Muddaththir (Chapter 74), Verses 2-7 According to Nasir al-Din Abu al-Khair Abdullah in the Tafsir Anwār At-Tanzīl wa Asrār At-Ta’wīl - Nesa Novrizal; Heru Saiful Anwar (Journal of Islamic Civilization, 2024)
The low quality and deviant attitudes of educators have led to a decline in the quality of education in Indonesia. Educators, in fact, play a crucial role in building an advanced and high-quality nation. Therefore, educators are expected to develop traits that align with the teachings of the Qur'an, which serves as the primary source of Islamic education. This study aims to identify the traits of ideal educators as outlined in Surah Al-Muddaththir, verses 2-7, according to Nasir al-Din Abu al-Khair Abdullah in his tafsir Anwār At-Tanzīl wa Asrār At-Ta'wīl. Additionally, it seeks to determine how these traits can be implemented by educators in Indonesia to improve the quality of education. The results of this research are expected to contribute significantly to the field of education, especially Islamic education. Moreover, the findings are anticipated to serve as guidelines in the development of educational curricula and policies. This discussion is based on library research, where data is gathered from sources relevant to the topic, including written sources and other literary references. Data collection is conducted using the documentary method, and the analysis is performed using content analysis.